Israel and Hamas at war: what price peace? - Anderson, Lawrence (2023)
Six weeks after Hamas’ surprise attack on 7 October, Israel has demolished much of Gaza City in the northern part of the Gaza Strip as well as substantial infrastructure elsewhere in the territory. Sustained military attacks has led to disproportionate casualties amongst civilian Palestinians and prompted urgent calls for a pause to the fighting. It does not appear either side can win but there is also no will to pursue peace via the two-state solution.